Sustainable geotourism using digital technologies along a rural georoute in Monsagro (Salamanca, Spain) - A. M. Martínez-Graña; L. Serrano; J. A. González-Delgado; C. J. Dabrio; P. Legoinha (International Journal of Digital Earth, 2017)
Rural geotourism looks at the natural resources of the territory as a means of promoting a specialized, educational, sustainable tourism. This is an increasingly sought-after activity. This paper presents a rural georoute across a high mountain village, highlighting the remarkable value of the geological heritage of biological trace fossils and physical sedimentary structures exposed on street pavements and façades of houses. A series of tourist georesources were created and implemented: educational and interpretive panels, videos, QR codes, geoapps and games, all of which promote and disseminate the exceptional geological content and the history of the earth through the use of new technologies (smartphones, ipod, etc.). All this is intended as a means to make geotourism a natural tourism, favoring experiences, whilst explaining the natural environment and its temporal and spatial dimensions, offering opportunities for socio-economic development and job creation in rural areas with problems of depopulation.